PEMBENTUKAN BUDAYA RELIGIUS SISWA MELALUI EKSTRAKURIKULER KEAGAMAAN DI MIS ISLAMIYAH LONDUT - Pasaribu, Ade Tia Melani Br (Jurnal Al-Fatih, 2024)
Religious extracurricular activities at MIS Islamiyah Londut are a method or process of instilling values derived from the teachings of Islam embraced by the students. These values are applied to shape the religious character of students who possess noble morals, righteous behavior, and ethics in accordance with Islamic teachings. This study uses a qualitative field method with data collection techniques in the form of interviews, observations, and documentation. The results of this study indicate that in the research location, efforts to instill and even spread religious values are linked with planned and controlled religious activities. The forms of activities meant include the development of student competencies (scouting, martial arts, and Qur’an recitation) which serve as a means to instill religious values in religious extracurricular activities. The values that are formed include values of worship, trust, sincerity, a spirit of jihad, morality, and exemplary behavior.